1986
DOI: 10.18474/0749-8004-21.2.175
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Ethology of the Southern Green Stink Bug, Nezara Viridula (L.), in Cowpeas

Abstract: A behavioral catalogue of the adult southern green stink bug, Nezara viridula (L.), was developed from observations taken in a cowpea field. A total of 23 behaviors are described, and the effects of sex, mating status, time of day, height on the plant, and substrate on these behaviors are quantified. Of the seven most common behaviors, which occupied 97% of the total observation time, sex significantly influenced the duration and/or frequency of kicking, rocking, and mating. Mating status significantly affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In general, the attractiveness of the trap crop and the presentation of trap crops in the field are important factors in attracting the insect and in the success of the trap cropping system (Velasco and Walter, 1992). Various trap crops have been recorded to attract pentatomid stink bugs (Knight and Gurr, 2006;Lockwood and Story, 1986;Mizell et al, 2008;Shelton and Badenes-Perez, 2006;Velasco et al, 1995;Velasco and Walter, 1992;Velasco et al, 1995). Shelton and Badenes-Perez (2006) are of the opinion that the potential of trap cropping significance would be greater if farmers, scientists and extension educators could expand their concepts of trap cropping to include more diverse modalities in their research.…”
Section: Trap Cropsmentioning
confidence: 99%
“…In general, the attractiveness of the trap crop and the presentation of trap crops in the field are important factors in attracting the insect and in the success of the trap cropping system (Velasco and Walter, 1992). Various trap crops have been recorded to attract pentatomid stink bugs (Knight and Gurr, 2006;Lockwood and Story, 1986;Mizell et al, 2008;Shelton and Badenes-Perez, 2006;Velasco et al, 1995;Velasco and Walter, 1992;Velasco et al, 1995). Shelton and Badenes-Perez (2006) are of the opinion that the potential of trap cropping significance would be greater if farmers, scientists and extension educators could expand their concepts of trap cropping to include more diverse modalities in their research.…”
Section: Trap Cropsmentioning
confidence: 99%
“…A previous study showed that adults and nymphs of N. viridula were observed to feed during early morning and late afternoon in the Þeld (Corpuz 1969, Lockwood andStory 1986); however, both of those studies were conducted during photophase. A previous study showed that adult female N. viridula could be seen feeding throughout the day, but fed for longer durations during scotophase (Ϸ12 min/h) than the photophase (Ϸ4 min/h) (Shearer and Jones 1996).…”
mentioning
confidence: 99%